A Critical Review of Zebrafish Models of Parkinson’s Disease - Doyle, Jillian M.; Croll, Roger P. (Frontiers in Pharmacology, 2022)
A wide variety of human diseases have already been modelled in zebrafish, including various types of cancer, cardiovascular disease and geriatric neurodegenerative disease like Alzheimer’s and Parkinson’s. Recent reviews have summarized the currently available zebrafish models of Parkinson’s Disease, which include both gene-based models and chemically induced models. The present review updates the literature, critically evaluates each of the available models and compares them with similar models in invertebrates and mammals to determine the benefits and drawbacks of Parkinson’s disease models in zebrafish. The review examines gene-based models, including ones linked to Early-Onset Parkinson’s Disease: PARKIN, PINK1, Dj-1, and Synuclein, but also examines LRRK2 which is linked to Late-Onset Parkinson’s Disease. We also evaluated chemically induced models like MPTP, 6-OHDA, Rotenone, Paraquat, and newer models like Metronidazole, titanium dioxide nanoparticles and heavy metals. These chemical models provide the opportunity to investigate the toxicology of environmental pollutants in an aquatic species. The review also investigates the unique advantages of zebrafish, including the abundance of behavioural assays available to researchers and the efficiency of high-throughput screens. These two attributes are particularly advantageous for potential pharmacological interventions. The review also weighs the drawbacks of the use of zebrafish including the difficulty of creating reliable and constant gene-based models, especially in an organism that has a duplicate genome. The goal of this review is to determine the benefits of using zebrafish for each of these Parkinson’s specific models and what advantages can be gained in comparison to utilizing other animals, as well as to investigate the limitations of zebrafish for investigating human disease.